Allelotoxic effect of parthenin on cytomorphology of broad bean (Vicia faba L.) - K.M. Abdul Raoof (Journal of the Saudi Society of Agricultural Sciences, 2013)
Parthenin is a natural constituent of Parthenium hysterophorus with phytotoxic and allelopathic properties. The present experiment was undertaken to determine the allelotoxic effect of parthenin on cytomorphology of Vicia faba L. The seeds were treated with different concentrations (100, 200, 300 and 400 μM) of parthenin for 8 h. The higher concentrations significantly reduced germination and seedling growth. A significant reduction in mitotic index was observed in seeds exposed to parthenin compared to control which decreased with an increase in concentration of parthenin. On the basis of these results, it was concluded that all parthenin concentrations significantly affect the cytomorphology of V. faba, while higher concentrations of parthenin were found to be more mutagenic and cytotoxic.